IMPLEMENTASI CORPORATE CULTURE “AKHLAK” DALAM UPAYA MENINGKATKAN KINERJA KARYAWAN DI MASA PANDEMI COVID-19 (STUDI PADA PT JASA MARGA BELMERA) - Muhammad Wisnu Wijaya Aditama; Dharmawan Sriyanto; Nicholas Marpaung (Awatara Publisher, 2023)
Company culture refers to the values and norms within an organization that serve as guidelines for employees. State-owned enterprises (BUMN) need to innovate to compete with private companies, including the transformation of human resources. In Indonesia, BUMNs like PT Jasa Marga Belmera adopt the